Lithostratigraphic Correlation of the Middle Eocene–Upper Miocene Rocks between Sectors (1-5), Tansulukh Region, Al Jabal Al Akhdar NE Libya: An Integrating Study from Previously Studied Wadies - B. Elfigih, Omar; E. El Qumati, Abobaker; Abdulrahman, Farag; Al hadad, Ahmed; Bukhamada, Abdulbaset; Gneiber, Omar (Libyan Journal of Science &Technology, 2022)
Some new lithostratigraphic measures are introduced for the nature of existence or removal of some rock units between some studied wadies in Tansulukh area. Lithostratigraphic correlation of the exposed rock units (Middle Eocene-Upper Miocene) between sectors 1-5 in Tansulukh region was necessary to be conducted because of the suspected rock complexities between these sectors. According to the conducted lithostratigraphic correlation between studied sectors (1-5) the missing of OligoceneMiddle Miocene rock units toward sectors 4 & 5 was attributed to some paleo-structural instability during post Eocene till pre-Late Miocene times.